Agrobiodiversity Index Report 2019: risk and resilience - Bioversity International (Bioversity International, 2019)
The first Agrobiodiversity Index Report assesses dimensions of agrobiodiversity in ten countries to measure food system sustainability and resilience. Countries receive an overall Agrobiodiversity Index score that indicates their progress in using and safeguarding agrobiodiversity to create sustainable food systems. They receive also individual scores for their progress for healthy diets, sustainable production and genetic resource conservation.